The Post-Apocalyptic Space, Character, and Morality in Middle-Grade Children’s Literature - Vlad Marinescu (Leaf Journal)
Stories for young readers overwhelmingly aim to educate on what is good and how a person must behave as a moral member of society. The question of how characters may further solidify moral right and wrong in the post-apocalyptic setting of my story The Neverending Sea became a focus for my research. Through this paper, I present: the discoveries made on the importance of children’s spaces in the post-apocalyptic; how characters can present a reader with moral dilemmas from the safety of the page, and perhaps, how they can be used to socialise young readers’ sense of right and wrong.